Sistemas nanoestruturados contendo óleo essencial de Melaleuca alternifolia: desenvolvimento de formulações e atividade biológica - Flores, Fernanda Cramer (2011)
The aim of this work was the development of nanostructured formulations containing M. alternifolia essential oil. Polymeric nanocapsules and nanoemulsions (10 mg/mL) were prepared by the interfacial deposition of preformed polymer method and spontaneous emulsification, respectively. The formulations were evaluated in relation to their physicochemical characteristics (particle size, polydispersity index, zeta potential, pH and oil content). Formulations presented oil content of about 96%, nanometric mean size (160-220 nm), polydispersity index below 0.25 and negative zeta potential. The pH values were 6.43 ± 0.37 and 5.98 ± 0.00 for nanoemulsions and nanocapsules, respectively. The inclusion of oil in nanocapsules showed higher protection against volatilization. The analysis of mean size and polydispersity index of the formulations presented no significant alteration during 60 days of storage time (at 25 °C, protected from light). The in vitro antifungal activity of the formulations was evaluated through the study of the inhibition growth profile of Candida albicans yeast. In addition, the antifungal activity against Trichophyton rubrum was studied using two different in vitro models of dermatophyte nail infection. The effect of nanostructures on the growth curve of C. albicans showed inhibition and control of its growing. Nail infection models demonstrated the ability of the formulations in reducing the T. rubrum growth, and the inclusion of oil in nanocapsules was more efficient. The development of hydrogels containing the nanostructured systems were carried out. The semisolid formulations showed adequate properties for topical administration. The topical antiedematogenic effect was evaluated by ear thickness measurement before and 24 h after UVB radiation. Hydrogels containing the colloidal systems showed effect, unlike to hydrogel containing the free oil. The in vivo healing effect of hydrogels was evaluated by regression of the wound in the rat skin. Hydrogel containing the nanocapsules presented higher activity in comparison to the positive control (hydrogel containing allantoin). Analyses of the oxidative stress showed an increase of glutathione, vitamin C and catalase levels after the treatment with the hydrogel containing the nanocapsules prepared with melaleuca essential oil.